Permainan Tradisional Hadang Dalam Mengembangkan Kemampuan Afektif Pada Anak Usia Dini di TK Islam Nur Amalia Penajam - Fitrianor Fitrianor; Noorthaibah Noorthaibah; Edy Murdani (Departement of Mathematics Education, 2023)
Children's affective ability to cooperate with others is still lacking, this is due to a lack of habituation or learning strategies aimed at developing these values. In addition to the lack of ability to work together in terms of managing emotions, it is also lacking, where children still express anger by hitting friends or screaming and crying. This happens because in learning activities more emphasis on cognitive aspects of learning. This study aims to describe the traditional game of hadang in order to develop the affective abilities of early childhood. The results of the study stated that traditional games as developed in Nur Amalia Penajam Islamic Kindergarten are an effective learning strategy for teaching children so that children are able to develop their affective aspects. Affective aspects developed include: cooperative attitude, sportsmanship, responsibility, and friendship. In the context of cultivating a successful affective aspect, the exemplary aspect of educators cannot be abandoned, because children will always imitate their educators in acting every time.